2020
DOI: 10.1038/s41433-020-1029-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lockdown on retinal detachment incidence in Scotland

Abstract: Wickham et al. [1] have highlighted the impact of COVID policies on ophthalmology services. Their findings are supported by our experience in Scotland. Rhegmatogenous retinal detachments (RRDs) are acute conditions that require prompt surgery [2]. The annual incidence of RRDs in Scotland was reported as 12.05/100,000 in 2010 [3]. The SARS-CoV-19 outbreak has been unprecedented. Healthcare services have worked hard to stay afloat. Subspecialty care has taken a back seat to intensive care and acute COVID wards. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
18
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 3 publications
7
18
3
Order By: Relevance
“…Shams et al reported a decrease in the cases of retinal detachment (RD) presenting to eye departments in Scotland suggesting that some cases of RD were left untreated during the lockdown period (10). In contrast, we have found increased cases of retinal detachment during the CP (N = 22) compared to the PCP (N = 19).…”
Section: Discussioncontrasting
confidence: 67%
“…Shams et al reported a decrease in the cases of retinal detachment (RD) presenting to eye departments in Scotland suggesting that some cases of RD were left untreated during the lockdown period (10). In contrast, we have found increased cases of retinal detachment during the CP (N = 22) compared to the PCP (N = 19).…”
Section: Discussioncontrasting
confidence: 67%
“…Contrary to other reports from the United Kingdom and North America 11 , 12 , 13 , 14 , 16 citing a significant reduction in the total volume of RDs seen over a 3- to 5-month period from the onset of the pandemic, we continued to treat a high volume of patients for the 6 months after March 14, 2020 ( Fig. 1 ).…”
Section: Discussionmentioning
confidence: 72%
“…Previous literature has suggested that RDs occurred less frequently during the COVID-19 pandemic owing to reduced patient activity and fewer opportunities to disturb the vitreous interface from eye surgery or trauma. 11 , 14 , 16 Although this may be true, other factors are likely to be more significant based on our results. The significant shift in the percentage of macula-off RDs suggests that, despite stable volumes of RDs over time, patients were waiting longer before seeking care.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“… 12 Similarly, across all vitreoretinal units in Scotland, a 55% decrease in the number of retinal detachments was seen in the five weeks following introduction of lockdowns (March 25, 2020 to April 29, 2020) compared to the average of the four five-week periods (excluding Christmas and New Year) leading up to March 25, 2020. 20 These changes may reflect issues beyond decreased incidence as outlined.…”
Section: Discussionmentioning
confidence: 99%